Understanding The Causal Pathways of Mental Health Symptoms in Indonesia - Syifa, Rahmatu; Ismah, Zata; Anelia, Astia; Mafaz, Zhafira; Nasution, Citra Cahyati; Yuliana, Roma; Pratiwi, Dessy (Jurnal Promkes: The Indonesian Journal of Health Promotion and Health Education, 2025)
Background: Mental disorders affect an individual's ability to cope with life stress, pursue education, work, and contribute to society. Among individuals of productive age, the prevalence of mental disorders reaches 15%. Factors such as age, education level, and gender play a role in influencing vulnerability to mental disorders in this age group. Objective: . This study aims to screen mental disorders experienced by the Indonesian population and analyze the causal factors of various mental disorder symptoms. Methods: This research is a quantitative observational-analytic study with a cross-sectional design. The study was conducted across all regions of Indonesia in 2023. A total of 2,081 Indonesian residents aged 18 and above participated in this study. Primary data were collected online via Google Forms. The collected data were analyzed univariat, bivariat using chi-square, multivariate using logistic regression, followed by path analysis. Results: The results showed that 84.2% of the participants experienced mental health disorders out of 2,081 respondents. Three variables were identified as the most vulnerable to mental health symptoms among the Indonesian population: female gender, low education level, and productive age (17–35 years). These variables were found to impact different mental health symptoms, such as anxiety, substance abuse, psychotic disorders, and post-traumatic stress disorder (PTSD). Specifically, individuals aged 17–35 years were more susceptible to anxiety, psychotic disorders, and PTSD. Women were more vulnerable to anxiety, substance abuse, psychotic disorders, and PTSD. Meanwhile, individuals with low education levels were more prone to anxiety and psychotic disorders.Path analysis revealed that psychotic symptoms serve as the culmination of three mental health symptoms. Conclusion: Mental disorder symptoms must be detected and treated promptly, even in mild cases, as all mental disorder variables have the potential to develop into psychosis, which manifests as physical illnesses resulting from psychological disturbances.